FACTORS INFLUENCING THE SIGNS OF LONGEVITY DAIRY COWS – REVIEW - Khmelnychyi, Leontii; Ponomarov, Yurii (Bulletin of Sumy National Agrarian University. The series: Livestock, 2025)
The article presents an in-depth analysis of the results of research by domestic and foreign scientists, conducted in the direction of studying problematic issues related to the influence of genotypic and paratypic factors on the traits of the duration of productive use and lifetime productivity of dairy cows. Genetic factors influencing longevity traits (breeding method, line, bull-sires, heredity by improving breed, degree of kinship, heritability, correlative variability) and paratypic (productivity, age of first calving, service period) were considered. World practice shows that increasing the genetic potential of dairy cattle productivity accompanied by negative consequences associated with a simultaneous decrease in reproduction characteristics, deterioration of udder and limb health, which leads to an increase in premature culling and a reduction in the traits of cows’ longevity. An important genetic factor, which, according to numerous studies, has an effect on longevity traits of dairy cows, is linear breeding, because of which successful combinations of linear and interlineal selection were used. The strength of line influence on life expectancy indicators, productive use, lactation and number of lactations during life in cows of Ukrainian Red-and-White dairy breed was 16.9–17.7%, and on the lifetime milk yield and milk fat amount in animals of Holstein breed – 18.6–22.4%. About the influence of bull-sires heredity and the types of parental pairs’ selection on the lifetime productivity of cows in different breeds reported by studies of domestic and foreign authors. A particularly important factor is inclusion of longevity traits in the selection index for assessing sires based on the quality of their offspring. The established existence of a positive correlation between the milk yield of the first lactation and the traits of longevity indicates the implementation, with the appropriate measure of efficiency, of effective indirect selection based on indirect predictive traits of first-born cows with the aim of selective improvement of longevity traits of the dairy cows. Most studies examining the effect of the age of first calving on longevity indicators report that too early (under 21 months) and late (over 29 months) calvings mostly lead to a reduction in both the duration of productive use and a decrease in the lifetime productivity of animals. According to the evaluation of cows of Ukrainian dairy breeds and the world in terms of reproductive capacity, it was established that the duration of service period significantly exceeds the optimal level in 80 days. With the growth of service period, indicators of longevity decrease with the strength of influence on life expectancy, productive use and lactation of cows by 12.5–36.5%, on lifetime productivity – 9.7–34.6, on milk yield per day of productive life use and lactation – 11.3–35.9%. The positive correlations between linear traits of the conformation and the functional longevity of cows from various breeds revealed in numerous studies indicate that they are good indirect predictors of the duration of productive life, and the degree of their heritability ensures effective selection in the direction of dairy type.